Effect on Compression Molding Parameters in Mechanical Properties of MWCNT/Glass Fiber/Epoxy Composites. (18th July 2022) - Venugopal, Jayaprakash; Dhanasakkaravarthi, B.; Surakasi, Raviteja; Rinawa, Moti Lal; Manjunatha, L. H.; Alshgari, Razan A.; Wabaidur, Saikh Mohammad; Islam, Md Ataul; Jenish, I.
Abstract : Reinforcing fibers, nanofillers, matrix materials, and manufacturing techniques all have a role in the mechanical characteristics of hybrid composites. MWCNTs-reinforced E-glass/Kevlar/epoxy composites are appropriate fillers for structural applications. The impact of different concentrations of MWCNT fillers (0.4%, 0.8%, and 1.2% wt) on the mechanical characteristics of hybrid composites has been studied. Tensile and bending strength, as well as hardness, were measured in compression-molded composites. The effects of compression pressure, mold temperature, and applied pressure on hybrid (0.8% MWCNT) were investigated. When it came to composite tensile and bending strength, compression pressure was the most important factor, closely succeeded by mold temperature and pressure period. Compression molding were optimized, resulting in a tensile strength of 183 MPa, a bending strength of 158.3 MPa, and a hardness value of 23.8 HV.